Angka kuman udara ruang rawat inap anak dengan dan tanpa air conditioner (AC) di rumah sakit - Raimunah Raimunah; Leka Lutpiatina; Jasmadi Joko Kartiko; Wahdah Norsiah (Politeknik Kementerian Kesehatan Banjarmasin, 2018)
Air microorganisms can be found in outdoor or indoor air, ventilation is a very important place in the exchange of indoor air. Ventilation system is divided into two, namely natural ventilation and artificial ventilation in the form of Air Conditioner (AC). This study aims to determine the description of the number of germs in the inpatient wards of children using Air Conditioner (AC) and non (AC) at the Hospital in Martapura city area. This type of research is descriptive survey, the population is the inpatient room of children using Air Conditioner (AC) and non (AC). Sampling using purposive sampling technique, that is as much as 8 room. The examination method used is by TPC (Total Plate Count) method. The results showed that the number of airborne bacterial infections using the Air Conditioner (AC) was 406 CFU/m3. The total number of non-living inpatients (AC) is 443 CFU/m3. The standard maximum number of microorganisms (CFU / m3) of treatment room according to Kepmenkes No.1204/ Menkes/SK/X/2004 is 200-500 CFU / m3.